Strength of kaolinitic clay soil stabilized with lime and palm oil fuel ash - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Wafiyuddin, Md Jariman (Penerbit UMP, 2024)
The use of palm oil fuel ash (POFA) mixed with lime as a catalyst in soil stabilization can significantly improve the stability of problematic soils and improve their engineering properties. Problematic soils can obstruct the construction process due to its low strength and low bearing capacity. In this study, various laboratory tests were carried out to determine the engineering properties of the soil’s mixture which includes Atterberg limit, particle size distribution, compaction, and unconfined compression test. 4%, 8% and 12% POFA were mixed with 6% hydrated lime to stabilized the kaolinitic clay soil at different curing days (1, 7, 14, and 30 days). Compared to untreated kaolin, the addition of POFA plus lime resulted in higher undrained shear strength. The maximum undrained shear strength (USS) is 32.68kN/m2, which was obtained on the 30th day of curing with the optimal mixture of stabilized kaolin which is kaolin mixed 6% of lime and 12% of POFA. The unconfined compressive strength increased by 185.04% compared to the unconfined compressive strength of untreated kaolinitic clay with a value of 65.36 kN/m2. This proves that kaolin stabilized with lime and POFA can increase the strength parameters of clay, thus reducing construction costs for soil stabilization and reducing environmental issues.